PENGARUH INDEPENDENSI DAN PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK - Amrulloh, Amrulloh; Putra, Yuniarti Hidayah Suyoso (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Public accountants are independent auditors who provide services to public, especially in the field of audit of financial statements made by the client. Public accountant’s task is to examine and provide an opinion on the fairness of financial statements of an entity based on the standards set by the Indonesian Institute of Accountants (IAI). Afflicting many companies which in turn involve public accountants, financial cases make the accountants to consider their audit quality. Some factors have a very important role in determining the audit quality, including the auditor independence and experience. Therefore, the issues examined in this study are: (1) Do the auditor’s independence and experience simultaneously have an influence on the quality of the audit? (2) Do the auditor’s independence and experience have a partial effecton audit quality? From that background, this research aims to (1) determine the simultaneous effect of auditor’s independence and experience on the quality of audit, (2) determine the partial effect of auditor’s independence and experience on the quality of audit. This research employs a survey method with questionnaires. The population of this research consists of auditors who work in Public Accounting Firm (KAP) in Malang. Data analysis is performed with validity and reliability test, and classical assumption test whereas hypothesis test with multiple linear regression method. The researcher uses and obtains the primary data by distributing questionnaires to 33 respondents. The result concludes that independence has a partial effect on the quality audit with significant level of 2,049. Simultaneously, the independence and the experience of the auditors affect the audit qualitywith significant level of 8,645. Therefore, both the auditor and the Public Accounting Firm (KAP) are expected to improve their audit quality.